(untitled) (Indian Journal of Arid Horticulture, 2013)
Horticultural produces grown in Rajasthan are of explicit quality with great nutritional, meditational and economic importance. Some of the fruit like aonla, jamun, tamarind, phalsa, custard apple, karonda, kainth and bael etc. and vegetables such as kachri, beans, bakla, kakora, guar and moringa etc. are successfully grown with minimum care on waste land and provide food and nutritional security to the rural masses.